2006
DOI: 10.1097/01.jom.0000214357.14677.5a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Social Predictors of Application for Social Security Disability Insurance by Workers??? Compensation Claimants With Low Back Pain

Abstract: Application for SSDI among claimants with occupational low back pain is associated with social factors like race, satisfaction, and socioeconomics as well as clinical factors like diagnosis and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…In particular, lower SES was associated with poorer long‐term adjustment even after controlling for baseline adjustment. Race was predictive of baseline adjustment and the WC process factor, a finding consistent with previous studies of this cohort [8,27,53–55], as well as long‐term adjustment as mediated through lower SES and poorer baseline adjustment. Thus, the associations of race were somewhat attenuated 6 years after claim settlement, whereas the significance of the SES association remained, although with a somewhat reduced magnitude over the long term.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, lower SES was associated with poorer long‐term adjustment even after controlling for baseline adjustment. Race was predictive of baseline adjustment and the WC process factor, a finding consistent with previous studies of this cohort [8,27,53–55], as well as long‐term adjustment as mediated through lower SES and poorer baseline adjustment. Thus, the associations of race were somewhat attenuated 6 years after claim settlement, whereas the significance of the SES association remained, although with a somewhat reduced magnitude over the long term.…”
Section: Discussionsupporting
confidence: 89%
“…One could conclude that Black patients received more consistent care, whereas White patients received variable care and in some instances may have been over treated. Similar results were found by Chibnall et al [9,10] where lumbar surgery rates for White but not Black Workers’ Compensation claimants exceeded normative rates. Barring a clear standard of pain care, it is difficult to adjudicate these two interpretations.…”
Section: Discussionsupporting
confidence: 89%
“…36 The DOLOR study identified that these socioeconomic factors are associated with worse outcomes among WC patients, such as applying for long-term disability through the Social Security Disability Insurance program. 33 This study confirms that such differences exist and their magnitude is large. Future work should examine the impact of controlling for such differences in studies assessing clinical and disability outcomes over time.…”
Section: Discussionsupporting
confidence: 76%
“…Since SPORT and NSN were not specifically designed to examine disability populations, limited baseline questions were available about psychosocial and work characteristics potentially related to disability compensation status. 33 To create a large, multistate sample of patients WC, we included patients from very different clinical studies, NSN and SPORT. Although we carefully developed eligibility criteria for NSN patients to mirror those in SPORT, it is possible that those found eligible may still be different in important but immeasurable ways.…”
mentioning
confidence: 99%